EU and Turkish competition law: a comparison - Türker, Bahar (My University, 2018)
Bu tezin amacı Avrupa Birliği ve Türkiye’deki hukuk sistemlerini rekabet hukuku ışığında incelemek ve bu iki sistemin benzerlikleri ile farklılıklarını hukuki ve tarihsel arka planları da göz önünde bulundurarak ortaya koymaktır.Bu tezin konusu yalnızca her iki hukuk sisteminin uygulama yöntemleri ve birbiri ile uyumluluk seviyesini ortaya çıkarmak değil, aynı zamanda aralarındaki uyumluluğu arttırabilmek adına hayata geçirilebilecek yenilikleri de öngörebilmektir. Dolayısıyla bu tez, Avrupa Birliği ve Türkiye’deki rekabet hukuku sistemlerinin birbiri ile uyumunu iyileştirmeye yönelik çözüm önerilerini de sunmayı amaçlamaktadır.

The objective of this study is to analyse the European Union and Turkish legal structures within the light of competition law and define similarities, as well as differences in between these regimes together with their historical backgrounds. The subject of this study is not only to identify the application methods of both sistems and to define the level of harmonization in between these two likely regimes, but also to forsee possible improvements to enhance the coherence in European Union and Turkish legal acquis. Therefore this thesis aims to present possible solutions to enrich the harmonization of the European Union and Turkish competition systems.
Keywords: Avrupa Birliği; Avrupa Birliği ülkeleri; Competition; European Union; European Union countries; Hukuk; Law; Law and legislation; Rekabet; rekabet hukuku competition law; Yasa ve yasama